Vacuum Effect on the Lactide Yield; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Yarkova A. V. Anna; Novikov V. T. Viktor Timofeevich; Glotova V. N. Valentina Nikolaevna; Shkarin R. V. Roman Vladimirovich; Borovikova Ya. S. Yana (2015, 2015)
Title screen